ANALISIS PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK, BRAND IMAGE DAN PERCEIVED VALUE TERHADAP MINAT BELI ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Rumah Makan Pondok Bandeng BaBe Kabupaten Pati) - Nyarmiati, Nyarmiati; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2021)
This study aims to examine the effect of service quality, product quality, brand image and perceived value on repurchase intention through customer satisfaction as an intervening at Pondok Bandeng BaBe Pati Restaurant. In this study the population taken was consumers who had made a purchase at the Pondok Bandeng BaBe Pati Restaurant with a total sample of 150 respondents who were selected using purposive sampling technique. Furthermore, the data obtained were processed using the AMOS 21 program. The results showed that service quality, product quality, brand image and perceived value had a positive and significant effect on customer satisfaction. Then customer satisfaction also has a positive and significant influence on repurchase intention at Pondok Bandeng BaBe Pati Restaurant.